PRINSIP VARIASI VAN BAAK SEBAGAI METODE ALTERNATIF DARI TEOREMA SIMPAL KIRCHHOFF UNTUK MENYELESAIKAN PERSOALAN-PERSOALAN RANGKAIAN LISTRIK ARUS SEARAH - Tayubi, Yuyu R.; Suhandi, Andi; Kaniawati, Ida; Noor, Suhendiana (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2001)
This study compared teaching electric circuit by applying Van Baak Variation Principle and by applying Kirchhoff loop theorem in developing studentsâ ability to solve DC circuit problems. The study was conducted in one high school in Lembang, about eight km from Bandung to the north. Most of the students come from farmer families with social-economic class status between middle and low. Two intact classes were involved in the study. One class was taught to use van Baakâs variational principle, and the other one was taught to use Kirchhoff loop theorem to solve circuit problems. The result indicates that students performed significantly better in applying van Baak variational principle than Kirchhoff loops theorem to solve complex electric circuit problems. No difference was found in student performance for simple circuits.Â Â Keywords: Van Baak variation principle, Kirchhoff loop theorem, DC electric circuit.